LEGITIMIZING STRATEGIES IN JAPANESE PEDAGOGICAL DISCOURSE (BASED ON THE COURSE OF MORAL EDUCATION) - Kozachina Anna V. (Актуальные проблемы филологии и педагогической лингвистики, 2018)
The paper is dedicated to legitimizing strategies in Japanese pedagogical discourse and aimed at studying Japanese pedagogical discourse (based on “The Course of Moral Education”) in the light of legitimizing strategies. Relevance and novelty also depends on lack of description of Japanese educational discourse in academic literature and its precedential texts are always studied in the light of pedagogic and culturology. As a result of the study, the main areas of Japanese education policy and the worldview values, implicitly transmitted to the young generation are reviled.